Pelaksanaan Tanggung Jawab Nakhoda Kapal atas Kerusakan Kapal dalam Pengangkutan Penumpang Antar Wilayah Kabupaten Natuna di Pelabuhan Rakyat Midai - Rezeki, Selpi Putri; Rani, Marnia; Syahputra, Irwandi (Penerbit Goodwood, 2023)
Purpose: There is a problem that occurred in Natuna Regency where a ship experienced engine damage, causing the ship to come to a halt in the middle of the sea and leaving passengers stranded at sea for an extended period. This situation can be hazardous and poses a risk to maritime safety. During disasters such as ship sinking, grounding, or fires, the risk to passenger safety increases. The high demand for facilities and infrastructure in passenger transportation should be a top priority. This research was conducted with the aim of determining the captain's responsibility for passenger safety to prevent any negligence on the part of the skipper. Methodology/approach: The Normative-Empirical Law research method involves understanding law in terms of norms (rules) and the application of legal rules in actual behavior resulting from the enforcement of legal norms. The captain is required to adhere to all applicable rules and regu lations to ensure the ship's navigability, safety of the vessel, passenger safety, and cargo. The skipper is not permitted to embark on a journey unless the ship is adequately equipped and prepared, as referred to in Article 343 of the Criminal Code. Results/findings: Regarding the implementation of the captain's responsibility for ship damage during passenger transportation within the Natuna Regency area, the captain pays more attention to the operational conditions of the ship to avoid issues related to ship damage. Additionally, the sub-district head of Midai is advised to be more selective in transferring responsibility to the skipper of the KM Fisabilillah 1 ship.